2020
DOI: 10.3390/cells9122563
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A Orchestrates Cytoskeletal Structure, Cell Migration and Stem Cell Characteristics in Human Seminoma TCam-2 Cells

Abstract: Filamins are large dimeric F-actin cross-linking proteins, crucial for the mechanosensitive properties of a number of cell types. Due to their interaction with a variety of different proteins, they exert important regulatory functions. However, in the human testis the role of filamins has been insufficiently explored. Immunohistochemical staining of human testis samples identified filamin A (FLNA) in spermatogonia and peritubular myoid cells. Investigation of different testicular tumor samples indicated that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Previously, FLNA has been proven to regulate cytoskeleton structure and cell migration in organogenesis ( 47 ) and is also involved in multiple cellular pathways. It can be linked as an important factor in many cancer-promoting steps ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, FLNA has been proven to regulate cytoskeleton structure and cell migration in organogenesis ( 47 ) and is also involved in multiple cellular pathways. It can be linked as an important factor in many cancer-promoting steps ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…FLNA, the most abundant and widely expressed member of the filamin family, functions as a nonmuscle actin filament crosslinking protein [ 28 ] to stabilize the cytoskeleton and maintain the structural integrity of cells [ 29 ]. FLNA was shown to associate with multiple functional noncytoskeletal proteins and is involved in several pathways that regulate cell migration and adhesion and promote tumor progression [ 30 ]. For example, c-Met/AKT/FLNA/SMAD formed a positive feedback loop to enhance EMT, which contributed to 5-fluorouracil resistance in CRC cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…FLNA crosslinks actin laments and helps to stabilize the cytoskeleton network and supports cell integrity [31] . Several studies showed that FLNA associates with multiple functional non-cytoskeletal proteins and is involved in several unrelated pathways that regulate cell migration and adhesion and promote tumor progression [32] . Mengmeng Cheng et al demonstrated that c-Met-AKT-FLNA-smad formed a positive feedback loop to enhance EMT, which contributes to 5-FU resistance of CRC cells [33] .…”
Section: Discussionmentioning
confidence: 99%